Women Proficiency for Global Crises Management in Ethiopia - Debela Bedada, Mergitu (International Journal of Scientific Research and Management (IJSRM), 2020)
The COVID-19 virus is a new pathogen that is highly contagious, can spread quickly, and considered capable of causing enormous health, economic and societal impacts in any setting. According to WHO report, about (78%-85%) human-to-human transmission  of the COVID-19 virus is the household transmission have occurred in families. The main  purpose of this article is to assess the potential of women in crises management.  These findings suggest that, women leadership  has a potential advantage  in crises management mainly because,  women are on average more likely than men to adopt a relational approach to leadership. So that  Ethiopia, will  benefit more , hence the country’s  more than half of the population and 50% of top-level leaders are women as a golden opportunity for Ethiopia to easily overcome this pandemic crisis  by engaging a full potential of women at all levels. I recommend for Ethiopian government to use this acknowledged golden opportunity of  having  more women leaders especially at top-level and having women more than half of the population  by mobilizing this women force up  to family level to overcome this pandemic disease more better than any countries in the world.